PENGARUH PROGRAM PELATIHAN TERHADAP KECEPATAN MEMPEROLEH PEKERJAAN (Studi Kasus Dinas Tenaga Kerja Kabupaten Gresik Tahun 2018-2021) - Rusdiana, Vira; Ismail, Munawar (Journal of Development Economic and Social Studies, 2024)
This study aims to find out whether labor training can increase the opportunity to get a job or not. By taking a case study of manpower training organized by the Gresik Regency Manpower Office, this research found that programs is indeed able to shorten manpower to obtain employment. In addition, this study also reveals other findings, namely, first, age prolongs labor to obtain employment, second, work experience accelerates to obtain employment and, third, education has no effect on the speed of obtaining employment.